Epidemiology and Trend of HIV/AIDs in Yazd, a Province in the Center of Iran, 2011-2017 - Mohammad Hassan Lotfi; Mohammad Khajeh; Marjan pedarzadeh; Majid jafarzadeh; Ali Reza pourmazar; Masoud Sharifi; Saeed Hosseini (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The first case of HIV-infection in Iran was a hemophilic child who was infected by imported blood products in 1989. Since then, the HIV epidemic in Iran has undergone significant changes. This study investigated the time variations of the epidemiology of reported HIV/AIDS -infections during 2011-2017 in Yazd, Iran. Methods: This analytical cross-sectional study was carried out using the data recorded in health centers of Yazd province from 2011 to 2017. The data were collected from the records of 98 patients using a researcher-made checklist. The rate of newly reported HIV/AIDS by gender per 100,000 people was calculated. Results: Out of 98 reported HIV/AIDS cases, 56.1% were men, and 43.9% were women; 55.1% of cases were infected through sexual contact, 30.6% through the infected needle while injecting for drug use, 1.6% through mother-to-fetus transmission, 1.3% through tattooing, and 5.1% through the unspecified mechanism. During these years the rate of newly reported HIV/AIDS in Yazd was declining, and the predominant mode of HIV transmission was through sexual contact. Conclusion: Although the rate of  newly reported HIV/AIDS -infection in Yazd province has decreased, we believe that the primary mode of HIV transmission has shifted from drug injection to unsafe sex.